Antibacterial effect of Psidium guajava L and Psidium acutangulum Mart on Streptococcus mutans - Afonso, Josmary (2018)
Objective: To evaluate the in vitro antibacterial effect of Psidium guajava L. (P. guajava) and Psidium acutangulum Mart. ex DC (P. acutangulum) extracts on isolated strains of Streptococcus mutans and control strain ATCC 25175. Methods: The extracts were obtained from healthy and fresh guava fruits in their green and mature state of the mentioned species. The identification of S. mutans from samples of patients with cavitated caries lesions (code 5, ICDAS) and from the control strain was carried out on Mitis Salivarius agar, under conditions of anaerobiosis, at 37 °C, for 48 hours, observing blue, rough colonies, and susceptibility tests were carried out using the disc diffusion method with the extracts obtained. Results: S. mutans was sensitive to the P. guajava extract, both for the control strain and for the patient strain, observing the highest inhibition halo for S. mutans ATCC 25175, reporting 43.8% of inhibition. Conclusions: The extracts of the P. perteneacutangulum and P. guajava husks have antibacterial effect on S. mutans, representing an alternative option against this microorganism, being a possible complementary product to the prevention of the development of dental caries.